The economics of stone disease - Canvasser, Noah E.; Alken, Peter (World journal of urology, 2017)
The rising prevalence of kidney stone disease is associated with significant costs to healthcare systems worldwide. This is in part due to direct procedural and medical management costs, as well as indirect costs to health systems, patients, and families. A number of manuscripts evaulating the economics of stone disease have been published since the 2008s International Consultation on Stone Disease. These highlight costs associated with stone disease, including acute management, surgical management, and medical management. This work hopes to highlight optimization in care by reducing inefficient treatments and maximizing cost-efficient preventative strategies.
Published online: 20 January 2017
Gesehen am 02.07.2018